THE USE OF LOCAL WISDOM-BASED DISCUSSION METHODS TO IMPROVE STUDENT LEARNING OUTCOMES IN PKN SUBJECT OF CLASS IV SDN 30 NEGERI KATON - Parliyatun, Parliyatun; Ulil Azmi (PT. Antis International Publisher, 2025)
Objective: This research examines local traditions in Lampung customs in order to improve learning outcomes for grade IV elementary school students. Method: This research uses the discussion method for a better approach for students. The focus of this research is the character formed in Lampung traditional culture carried out by Lampung tribe people who live in Pesawaran Regency, Lampung Province towards improving learning outcomes in civic education subjects in elementary schools. This type of research is a classroom action research (PTK) conducted in 2 cycles. Each cycle consists of planning, implementation, observation and reflection. In this study, researchers identified the problems of student learning outcomes and gave 2 tests, namely the final test in cycle 1 and the final test in cycle 2. The objects in this study were 16 students from class IV SDN 30 Negeri Katon in the 2024/2025 academic year. Results: The results showed that local wisdom that is still often practiced in the community such as gotong royang and deliberation are noble values carried out by the community for generations can be used as an example in group discussions and integrated in learning at school. This study shows success based on an increase in student learning outcomes that can be seen from all activities in cycle 1 and cycle 2. Based on the results of cycle 1, it was found that 63% of students did not reach the Minimum Completeness Criteria (KKM), and for the results of cycle 2, 81% of students reached the minimum completeness criteria. Novelty: The results showed that local wisdom that is still often practiced in the community such as gotong royang and deliberation are noble values carried out by the community for generations can be used as an example in group discussions and integrated in learning at school.